Рolycultural Education as a Socio-Pedagogical Phenomenon - Paliyeva, Tatyana V. (International Dialogues on Education Journal, 2019)
The article analyses the conceptual foundations of polycultural education, both from a global philosophical and pedagogical point of view and using the example of the peculiarities of polycultural education in the Republic of Belarus. (The term “polycultural education” is understood in a similar way to “multicultural education” in the Anglo-American sphere or “interkulturelle Bildung” in the German language.) The author reflects on the use of different terminological concepts to illustrate the diversity of ideas regarding the purpose, nature and content of polycultural education and training in a multicultural world. The specificity of the theory and practice of polycultural education in Belarus is based on geographical, historical, denominational, cultural, sociolinguistic, social and pedagogical factors. At present, the Republic of Belarus is a practically multi-ethnic country with rather low migration. Nevertheless, the development of a multicultural personality is seen as an important task in preparing the younger generation for life in today’s society.